2013
DOI: 10.1182/blood-2013-03-491423
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for Lyn kinase in strengthening endothelial integrity and barrier function

Abstract: Key Points In contrast to c-Src and Yes, Lyn stabilizes endothelial junctions through interaction and phosphorylation of FAK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 54 publications
2
48
1
Order By: Relevance
“…The EC-expressed TLR4 plays a pivotal role in mediating the increased vascular permeability stimulated by LPS, which has been shown in many previous studies [2,41] and LPSinduced vascular permeability is often applied in the researches of endothelial integrity and barrier function [23] in tumor or inflammatory diseases. Therefore, we use LPS to stimulate HUVECs constructing the increasing vascular permeability model.…”
Section: Discussionmentioning
confidence: 95%
“…The EC-expressed TLR4 plays a pivotal role in mediating the increased vascular permeability stimulated by LPS, which has been shown in many previous studies [2,41] and LPSinduced vascular permeability is often applied in the researches of endothelial integrity and barrier function [23] in tumor or inflammatory diseases. Therefore, we use LPS to stimulate HUVECs constructing the increasing vascular permeability model.…”
Section: Discussionmentioning
confidence: 95%
“…G protein bg-dependent FAK activation localized the kinase to the AJ to promote resealing of the junctions and restore barrier function (22). Likewise, Han and colleagues (48) observed that small interfering RNA knockdown of FAK in human umbilical vein endothelial cells resulted in VE-cadherin breakdown at the endothelial cell border. Thus, the protective effect of FAK activation on the pulmonary vasculature, after SHP2 activation, may be mediated by the localization of FAK-SHP2 protein-protein interactions at the focal adhesion complexes, as well as AJs, in the endothelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, as Lyn is thought to be expressed primarily in hematopoietic cells. Lyn has been reported to be present in other epithelial cell types (35)(36)(37)(38). Lyn is unique in that it initiates both activating and inhibitory signaling in hematopoietic cells, with the inhibitory signaling role being dominant (25 Human airway epithelial cells have been reported to express TLR1-6 and -9 (39).…”
Section: Discussionmentioning
confidence: 99%